HyperSpector:VMM dynamic trusted monitor based on UEFI - Kai WANG; Zhi-hua LI; Fan, HUANG; Fei1 YAN (网络与信息安全学报)
With the rapid innovation of computer technology,cloud computing model expands.VMM was intro-duced to enhance the cloud safety and enhance the cloud safety.The safety of VMM itself,however,is the prerequi-site of the safety of the cloud service.A method of VMM dynamic trusted monitor based on UEFI was proposed on the purpose of enhancing the safety of VMM.The monitor of VMM was realized by adding a monitor layer beneath it,which needed no more newly hardware cost.Experiment results show that the solution is efficient.